Microencapsulated medium-chain fatty acids as an antibiotic alternative improve intestinal immunity and microbiota composition in weaned piglets - Zhang, Gang; Chen, Yifan; Huang, Jingyi; Lang, Jiashi; Shang, Mingzhu; Shao, Lei; Sun, Zhiqiang; Zhao, Jinbiao (Frontiers in Veterinary Science, 2026)
ObjectiveThis study aimed to evaluate effects of microencapsulated medium-chain fatty acids (MCFA) on growth performance, antioxidant capacity, immune response, and gut microbiota in weaned piglets.Materials and methodsA total of 120 weaned piglets (Initial BW 6.38 ± 1.03 kg) were randomly assigned to one of three dietary treatments for a 42-day trial: a corn-soybean meal basal diet (CON), a diet supplemented with 150 mg/kg colistin sulfate (AGP), or a diet supplemented with 0.15% microencapsulated MCFA (MOA), with 5 replicates of 8 piglets per treatment.ResultsDuring the overall period, the MOA group exhibited a higher average daily feed intake than both the CON and AGP groups (p < 0.05). Dietary MCFA supplementation significantly reduced (p < 0.05) diarrhea incidence in the first 2 weeks compared with the AGP group. On day 42, MCFA enhanced serum total antioxidant capacity compared with the AGP group and significantly lowered (p < 0.05) pro-inflammatory cytokines in the jejunum and colon compared with the CON group. On d 14, MCFA increased (p < 0.05) jejunal butyrate, lactate and jejunal and colonic total short chain fatty acids (SCFA) concentrations. Microbiota analysis revealed that MCFA modulated both jejunal and colonic communities, significantly enriching beneficial bacteria in the colon, such as Rikenellaceae_RC9_gut_group and Roseburia.ConclusionDietary supplementation with 0.15% microencapsulated MCFA promoted feed intake, optimized intestinal microbiota composition and metabolism, and alleviated intestinal inflammation in weaned piglets.